A Bioengineered Nisin Derivative, M21A, in Combination with Food Grade Additives Eradicates Biofilms of Listeria monocytogenes - Smith, Muireann K.; Draper, Lorraine A.; Hazelhoff, Pieter-Jan; Cotter, Paul D.; Ross, R. P.; Hill, Colin (Frontiers in Microbiology, 2016)
The burden of foodborne disease has large economic and social consequences worldwide. Despite strict regulations, a number of pathogens persist within the food environment, which is greatly contributed to by a build-up of resistance mechanisms and also through the formation of biofilms. Biofilms have been shown to be highly resistant to a number of antimicrobials and can be extremely difficult to remove once they are established. In parallel, the growing concern of consumers regarding the use of chemically derived antimicrobials within food has led to a drive towards more natural products. As a consequence, the use of naturally derived antimicrobials has become of particular interest. In this study we investigated the efficacy of nisin A and its bioengineered derivative M21A in combination with food grade additives to treat biofilms of a representative strain of Listeria monocytogenes. Investigations revealed the enhanced antimicrobial effects, in liquid culture, of M21A in combination with citric acid or cinnamaldehyde over its wild type nisin A counterpart. Subsequently, an investigation was conducted into the effects of these combinations on an established biofilm of the same strain. Nisin M21A (0.1 µg/ml) alone or in combination with cinnamaldehyde (35 µg/ml) or citric acid (175 µg/ml) performed significantly better than combinations involving nisin A. All combinations of M21A with either citric acid or cinnamaldehyde eradicated the L. monocytogenes biofilm (in relation to a non-biofilm control). We conclude that M21A in combination with available food additives could further enhance the antimicrobial treatment of biofilms within the food industry, simply by substituting nisin A with M21A in current commercial products such as Nisaplin (Danisco, DuPont).